Frequently asked questions about nonlinear dynamics and empirical dynamic modelling. (26th November 2019) - Munch, Stephan B; Brias, Antoine; Sugihara, George; Rogers, Tanya L
Abstract: Complex nonlinear dynamics are ubiquitous in marine ecology. Empirical dynamic modelling can be used to infer ecosystem dynamics and species interactions while making minimal assumptions. Although there is growing enthusiasm for applying these methods, the background required to understand them is not typically part of contemporary marine ecology curricula, leading to numerous questions and potential misunderstanding. In this study, we provide a brief overview of empirical dynamic modelling, followed by answers to the ten most frequently asked questions about nonlinear dynamics and nonlinear forecasting.